Application of Numerical Simulation on the Manufacturing Process Qualification of Nuclear Power Plant Steam Generator Tube-sheet - Zhang Shao Jun; Liang Shu Hua; Yang Wen Bin; Liu Zhao; Zhao Dong Hai (MATEC Web of Conferences, 2016)
Nuclear power plant key parts-steam generator (SG) tube sheet forging operate in harsh environment, so it has high requirements for internal quality. According to RCC-M specification requirements (take CPR1000 reactor type for example), the manufacturer should carry out workshop qualification and part process qualification before delivery product manufacturing. It is commonly used that centre compaction process and conical plate upsetting process regard as two kinds of large forging upsetting ways. The numerical analogue simulation has been carried out on nuclear power large tube sheet forgings using France Forge simulation software. The results show that: when the same pressure size, 3-direction compressive stress in the core of the billet always exist in the process of upsetting using centre pressing process, and the strain create in the central of the billet, but stagnant zone exist on the bottom and end plane; tensile stress in the core of the billet always exist in the process of upsetting using conical plate upsetting process, it will force the billet that contact with conical plate to deform, so eliminate stagnant zone, but effective deformation don’t produce in the central of the billet. The conical plate continue press for conical plate upsetting process, tensile stress in the core of the billet disappear, and then gradually change into pressure stress, then tensile stress is generated at the bottom, finally tensile stress disappear and 3-direction compressive stress exist in the core of the billet.